Economic and geopolitical analysis of the eastern mediterranean economic - İncekara, Rahmi (Akademisyen Kitabevi, 2020)
Chapter 1: Hydrocarbon Energy Resources And Naval Forces Of Littoral States In Eastern Mediterranean Chapter 2: While Nato Show Off Energy Security Via Securitization, Eastern Mediterranean Is In Nodus But Turkey? Chapter 3: A Catalytic Activity For A De Novo Modus Vivendi Between Turkey And Israel Chapter 4: A Modus Vivendi with the Emergence of the New Game Changer Between Israel and Turkey Chapter 5: Greece and the Energy Geopolitics of the Eastern Mediterranean